Law, Gender, and Higher Education in Madagascar: Confronting Sexual Harassment on Campus - Razafitahindraza Erica Feyzine Sulla; Rakotoniriana Noelisoa Jean Michel; Razafiharimbola Larissa; Shahabuddin Esmati (Universitas Islam Negeri Mataram, 2026)
This study aims to examine the intersection of law, gender, and higher education in Madagascar by analyzing sexual harassment in public universities, with a focus on the University of Toliara. Using a qualitative approach, data were collected from 50 key informants, including 40 students (from first-year to doctoral level), 5 lecturers, 3 administrative staff members, and 2 lawyers selected through purposive sampling. Findings reveal that sexual harassment is closely linked to hierarchical power relations, with cases of conditional or quid pro quo practices tied to academic evaluation, disproportionately affecting female students. The study also identifies significant gaps between legal frameworks and institutional practices, alongside strong barriers to reporting such as stigma and fear of retaliation. These results highlight the need for strengthened legal enforcement, transparent institutional mechanisms, and gender-sensitive policies. The study contributes to legal and educational scholarship by emphasizing the role of universities as critical spaces for advancing gender justice and safe learning environments